Chemical Composition of the Essential Oils in Portuguese Daucus Carota Subspecies - Silva, Sofia; Barata, Jasmine; Lopes, Violeta; Barata, Ana; Gomes, Arlindo; Silva, Lúcia; Luísa Fernando, Ana (KnE Materials Science, 2022)
This study focused on five different subspecies of Portuguese Daucus carota L., to identify the main compounds in the essential oils of umbels from each subspecies. The isolation of the essential oils was performed by hydrodistillation methods followed by further composition analysis by gas chromatography-mass spectrometry, ultimately demonstrating that each subspecies had different major compounds. This study concluded that the main compounds found in Daucus carota subsp. maritimus were geranyl acetate, followed by trans-methyl-isoeugenol, α-pinene, cis-asarone and elemicin. Daucus carota subsp. hispidus presented with the major compounds as geranyl acetate, caryophyllene oxide, trans-methyl-isoeugenol and sabinene. For Daucus carota subsp. maximus, the major compounds were cis-asarone, geranyl acetate and elemicin, which was similar to Daucus carota subsp. carota which presented with the major compounds as geranyl acetate, cis-asarone, trans-methylisoeugenol and α-pinene. Finally, the major components of Daucus carota subsp. sativus were carotol and daucol. Keywords: essential oils, chemical composition, Daucus carota, hydrodistillation, GC-MS